Government employees ; Louie Ocampo ; Buko [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Features the unhealthy work culture in government offices, the effect on the plan of reorganization; interviews with Louie Ocampo, a music composer; and the Congress exposing the "buko" controversy.